2017
DOI: 10.15406/jnmr.2017.06.00152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Wavelengths on Drug Release with and without Gold Nanoshells and Magnetic Guidance on Uptake by Cancer Cells

Abstract: Liposomes containing Au coated Fe 3 O 4 referred to as magnetoplasmonic liposomes (MPL) and doxorubicin (L-Dox) are fabricated to investigate the effects of continuous and pulsed laser wavelengths on drug release from liposomes and magnetic guidance on the uptake of MPL by cancer cell line. Fluorescence microscopy was used to evaluate the apoptosis effect. A maximum temperature of about 6°C was achieved after 400 s for liposomes containing (magnetoplasmonic nanoshells) MPNSs at 100 µg/ml using 514 nm laser. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…8,[11][12][13][14] Moreover, it was shown that laser-sensitive liposomes could be functionalized by the laser beam to enhance the release of the cargo leading to cancer cell death. 15,16 The mentioned data pointing to laser stimulation could eventually induce cell apoptosis. 17 As laser photomodulation and irradiation on cells is one of the most widespread applications of a laser in medicine and it is being frequently used in LDDSs for cancer patients, investigating its effect on liposomal drug release is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…8,[11][12][13][14] Moreover, it was shown that laser-sensitive liposomes could be functionalized by the laser beam to enhance the release of the cargo leading to cancer cell death. 15,16 The mentioned data pointing to laser stimulation could eventually induce cell apoptosis. 17 As laser photomodulation and irradiation on cells is one of the most widespread applications of a laser in medicine and it is being frequently used in LDDSs for cancer patients, investigating its effect on liposomal drug release is of great importance.…”
Section: Introductionmentioning
confidence: 99%